2015
DOI: 10.5430/jha.v5n2p29
|View full text |Cite
|
Sign up to set email alerts
|

Review of e-portfolio requirements and methodology

Abstract: Background: Portfolios are used in medical practice as a means of instilling "reflective learning" in doctors and accumulating evidence of the doctor's competence. It is a mandatory requirement by the General Medical Council (GMC), as a form of public accountability, for licensed clinicians to maintain an e-portfolio of daily clinical practice, which is subjected to annual appraisals and ultimately influences their ability to renew their license to practise in the UK. This article reviews the reflective learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…17 Additionally, it is observed that the electronic databases, such as e-logbooks, are cost-effective and feasible tool for performance-tracking of medical students and allow medical professionals to maintain an online evidence of their experience, competencies and achievements, which serve as a valuable tool for the professional development. 18,19…”
Section: Discussionmentioning
confidence: 99%
“…17 Additionally, it is observed that the electronic databases, such as e-logbooks, are cost-effective and feasible tool for performance-tracking of medical students and allow medical professionals to maintain an online evidence of their experience, competencies and achievements, which serve as a valuable tool for the professional development. 18,19…”
Section: Discussionmentioning
confidence: 99%